POLITIK IDENTITAS DALAM PEMILIHAN GUBERNUR NUSA TENGGARA TIMUR 2013 DI KOTA KUPANG - Yohanes Yoelvan Negong (Program Magister Ilmu Politik, Universitas Diponegoro, 2017)
Identity politics is a concept and a political movement which the attention focus is difference as a major political category. In Indonesia the identity politics is more related to ethnicity, religion, ideology, and local interests that are generally represented by elites with their respective articulations, respectively. The direct local elections since 2005 have created an interesting phenomenon, when religious and ethnic-based politics are considered the strategic in attracting sympathy and support from the community. This research is aimed to find out the religion influence and ethnic on the voting behavior by Kupang society in the East Nusa Tenggara Governor and Vice Governor Election 2013. In this research is used Ethnic especially primordial theory by the instrumentalist approach, and religion especially religious and voting behavior approach in psychological and rational. The research method used is quantitative research method with multistage random sampling technique, with the primary data collection method using survey and document analyses as well as literature for secondary data. The results showed that religion and ethnic influence on the Kupang people voting behavior in the East Nusa Tenggara Governor and Vice Governor election 2013.